1994
DOI: 10.1037/h0095535
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences in caregiver adaptation: Focus on mental illness and brain injury.

Abstract: The purpose of this study was to explore potential differences among three groups of caregivers with a relative who had experienced a mental ill This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.Psychosocial Rehabilitation Journal ness or a head injury. Guiding questions included the following: 1) what dif ferences exist between the groups differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
3
10
1
3
Order By: Relevance
“…For example, family members with a higher level of education are likely to join support groups. This finding is consistent with those reported by other authors 79. Although none of these studies found differences between groups in terms of relationship with the disabled relative, our results suggest that more parents join support groups than siblings, spouses or adult children.…”
Section: Discussionsupporting
confidence: 94%
“…For example, family members with a higher level of education are likely to join support groups. This finding is consistent with those reported by other authors 79. Although none of these studies found differences between groups in terms of relationship with the disabled relative, our results suggest that more parents join support groups than siblings, spouses or adult children.…”
Section: Discussionsupporting
confidence: 94%
“…When compared with the ® ndings of previous research on other caregiving situations, this time lag seems to be a unique feature of parental caregiving for persons with schizophrenia. For example, research about caregiving in traumatic head injury that resulted in mental impairment has suggested that caregivers are likely to hear about the diagnosis and prognosis immediately or soon after the accident (Brady et al, 1994;Grant & Bean, 1992;Hall et al, 1994). Also, the model of transformed parenting proposed by Seideman and Kleine (1995) that was based on research with parents of children with developmental delay and mental retardation indicated that ª Parents described rapid movement through an entrance process that included their initial response to hearing the child' s diagnosisº (Seideman & Kleine, 1995, p. 44).…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of caregiving for adult children with traumatic brain injury are similar to those of caring for adult children with mental disorders (Brady, Goldman, & Wandersman, 1994). In both situations children making transitions to adulthood experience biopsychosocial impairments that limitself-care and independent living skills.…”
Section: Burden Stress and Care For Elders And Adultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A vast body of literature has demonstrated that mental illness and drug addiction are physically, economically, and mentally damaging not only to the individuals who experience these disorders, but also their significant others (Orford et al, ; Weisman de Mamani & Suro, ; Wilkinson & McAndrew, ). These consequences are referred to in the literature as objective and subjective burdens (Biegel et al, ; Brady et al, ). The objective burden is the tangible effect of caregiving on the life of caregivers, associated with their close contact with an individual with mental problems (e.g.…”
Section: Introductionmentioning
confidence: 99%